2017
DOI: 10.1007/s00775-017-1458-z
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt tetradehydrocorrins coordinated by imidazolate-like histidine in the heme pocket of horseradish peroxidase

Abstract: Horseradish peroxidase was reconstituted with cobalt tetradehydrocorrin, rHRP(Co(TDHC)), as a structural analog of cobalamin coordinated with an imidazolate-like His residue, which is generally seen in native enzymes. In contrast to the previously reported cobalt tetradehydrocorrin-reconstituted myoglobin, rMb(Co(TDHC)), the HRP matrix was expected to provide strong axial ligation by His170 which has imidazolate character. rHRP(Co(TDHC)) was characterized by EPR and its reaction with reductants indicates a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The large size of the enzyme causes challenges in elucidation of its reaction mechanisms . In this context, a cobalt tetradehydrocorrin derivative 8 was designed as a model of cobalamin, and rMb­( 8 ) was prepared and investigated as a hybrid model to replicate the reaction promoted by methionine synthase. The Co­(II) species of rMb­( 8 ) was first prepared, and its crystal structure revealed ligation of His93 to the Co center in the heme pocket (Figure ). Soaking the Co­(II) crystals in a dithionite solution successfully provided the crystals to the Co­(I) species.…”
Section: Non-natural Metalloporphyrinoid Cofactorsmentioning
confidence: 99%
“…The large size of the enzyme causes challenges in elucidation of its reaction mechanisms . In this context, a cobalt tetradehydrocorrin derivative 8 was designed as a model of cobalamin, and rMb­( 8 ) was prepared and investigated as a hybrid model to replicate the reaction promoted by methionine synthase. The Co­(II) species of rMb­( 8 ) was first prepared, and its crystal structure revealed ligation of His93 to the Co center in the heme pocket (Figure ). Soaking the Co­(II) crystals in a dithionite solution successfully provided the crystals to the Co­(I) species.…”
Section: Non-natural Metalloporphyrinoid Cofactorsmentioning
confidence: 99%
“…[1,2] Supramolecular systems have become increasingly complex, creating new opportunities for interfacing with biology. [3][4][5] As evidence of this,s upramolecular architectures have been generated that function as platforms for the dimerization, assembly,o rf unctional modulation of proteins,p roviding orthogonal control and reversible switching. [6][7][8][9][10] Theg eneration of orthogonal synthetic systems mimicking cellular components,v ia in vitro synthetic biological networks,c onstitutes al andmark objective.…”
Section: Supramolecular Control Over Split-luciferase Complementationmentioning
confidence: 99%
“…Electrocatalytic four electrons reduction of O2 to H2O by cobalt porphyrins has been extensively studied so far not only because of its biological relevance, but also due to its technological significance such as in fuel cells [21,22]. Furthermore, the studies of cobalamin and its derivatives/analogues have significantly contributed to increase the popularity of Co(II) complexes [23][24][25][26]. It was also found that the reactivity of axial ligation of cobalt porphyrin play a pivotal role in a number of bio-and 'bio-inspired' catalytic transformations.…”
Section: Introductionmentioning
confidence: 99%